2021
DOI: 10.3390/pediatric13020025
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Skin Lesions in Three SARS-CoV-2 Swab-Negative Adolescents: A Possible COVID-19 Sneaky Manifestation?

Abstract: Coronavirus disease 19 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is associated with various clinical manifestations, including skin lesions. In particular, during the COVID-19 pandemic lock-down period numerous chilblain-like lesions, mainly located on the feet, were observed in adolescents. The latter were often asymptomatic or associated with very mild respiratory symptoms. Here, we report three cases of acral nodular lesions in SARS-CoV-2 swab-negative adolescents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Andina et al [14] also described a case of a one-month-old baby girl with reticulated plantar purpura, negative to the molecular swab, but positive to IHC for SARS-CoV-2. We also, in another very recent work [15], described three cases of molecular test negative pediatric patients whose skin biopsies showed histological characteristics similar to those described in this new study, in the second group, who had tested positive for IHC for SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 73%
“…Andina et al [14] also described a case of a one-month-old baby girl with reticulated plantar purpura, negative to the molecular swab, but positive to IHC for SARS-CoV-2. We also, in another very recent work [15], described three cases of molecular test negative pediatric patients whose skin biopsies showed histological characteristics similar to those described in this new study, in the second group, who had tested positive for IHC for SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 73%
“…More than a year and a half after its inception, the severe acute respiratory syndromecoronavirus 2 (SARS-CoV-2) pandemic continues to affect the entire globe, posing new challenges and new questions, as important pathogenic mechanisms go on being discovered [1,2]. It has now been demonstrated that SARS-CoV-2 can affect different organs, featuring different manifestations and clinical pictures [3][4][5][6]. Surely, the fundamental relationship between pregnancy and SARS-CoV-2 was partially studied at the start of the pandemic, but it began to be more thoroughly investigated as new evidence came to the fore [7].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding skin involvement, reports of different eruption patterns became very frequent and numerous, both in the adult and pediatric population, first in China and then gradually throughout the globe [ 14 , 15 , 16 ]. Among the different cutaneous manifestations of COVID-19, erythematous rashes [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ], pseudo-chilblains [ 24 , 25 , 26 ], acro-ischemia and livedoid lesions [ 27 , 28 , 29 , 30 , 31 , 32 ] or other cutaneous manifestations resembling pityriasis rosea, erythema elevatum diutinum, erythema multiforme and Grover disease have been reported [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%